Regelbuch und Observanz - Engler, Claudia (De Gruyter, 2017)
the series plans to encourage research into the history of the literature, art and culture of the south-western German-speaking area. The methodology envisaged will work from manuscripts to direct attention to the social formations in which literature and art are produced, copied and received. The focus is on the Alemannic language area, thus on the monasteries, towns and cities of the Upper Rhine, Swabia and Switzerland.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Meyer; Johannes; Frühneuhochdeutsch; Handschrift; Ordensreform